Diversity of livestock associated methicillin-resistant Staphylococcus aureus - Tegegne, Henok A; Koláčková, Ivana; Karpíšková, Renata (Asian Pacific journal of tropical medicine, 2017)
OBJECTIVE: To evaluate the diversity and molecular characteristics of livestock associated methicillin-resistant Staphylococcus aureus in livestock animals, food of animal origin and the environment in the Czech Republic. METHODS: After having been primarily enriched in buffered peptone water, the samples were cultured on Baird-Parker agar. Presumptive colonies were sub-cultured to blood agar and assessed morphologically. Furthermore, presumptive Staphylococcus aureus colonies were confirmed by MALDI-TOF. Multiplex PCR, spa-typing, and MLST have been used to characterize the strains. Each mecA-positive Staphylococcus aureus isolates were examined against 14 different antimicrobials by using disk diffusion method. RESULTS: In this study, 13 different spa-types belonging to five sequence types (ST) were detected. Ninety four percent of tested strains belonged to CC/ST398 for which t011, t034, t2123 and t2346 were the vast major spa-types. In addition, non-ST398 clones such as CC1(t127), ST5(t3598), ST8(t064) and ST361(t315) were detected, which are known as human associated clones. CONCLUSIONS: The diversity of livestock associated methicillin-resistant Staphylococcus aureus has grown, and detecting lineages of human origin in animals and vice-versa becomes more common. Thus, livestock animal and its products will be a potential for the evolvement of methicillin-resistant Staphylococcus aureus in human population. Monitoring of pigs as well as other food-producing animal species and their products is therefore recommended.
Keywords: CC398; PCR; MLST; Spa-typing